The Exocyst Subunits EqSec5 and EqSec6 Promote Powdery Mildew Fungus Growth and Pathogenicity - Jinyao Yin; Xuehuan Zhu; Yalong Chen; Yanyang Lv; Jiaxin Shan; Yuhan Liu; Wenbo Liu; Weiguo Miao; Xiao Li (Journal of Fungi, 2025)
The exocyst complex in eukaryotic cells modulates secretory vesicle transportation to promote exocytosis. The exocyst is also required for the hyphal growth and pathogenic development of several filamentous phytopathogens. Obligate biotrophic powdery mildew fungi cause considerable damage to many cash crops; however, the exocyst’s roles in this group of fungi is not well studied. To verify the functions of the exocyst in powdery mildew fungus, we identified two exocyst subunits, EqSec5 and EqSec6, from Erysiphe quercicola, a powdery mildew fungus that infects the rubber tree Hevea brasiliensis. When GFP-fused EqSec5 and EqSec6 were introduced into E. quercicola and another phytopathogenic fungus, Magnaporthe oryzae, they primarily localized to the hyphal tip region. Inducing gene silencing of EqSec5 or EqSec6 caused growth and infection defects, and those defects could not be fully restored under the NADPH oxidase inhibitor treatment to the plant. The silenced strains also induced the host defense response including reactive oxygen species accumulation and callose deposition. The silencing of EqSec5 or EqSec6 also inhibited the secretion of the effector protein EqIsc1, interrupting plant salicylic acid biosynthesis. Yeast two-hybrid and gene overexpression assays suggested that EqSec5 and EqSec6 interact with each other and can complement each other’s function during host infection. Overall, our study provides evidence that the exocyst in this powdery mildew fungus facilitates effector secretion, hyphal growth, and infection.